Explaining the stylized facts of foreign exchange markets with a simple agent-based version of Paul de Grauwe's chaotic exchange rate model - Sarah Mignot; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2023)
We propose a simple agent-based version of Paul de Grauwe's chaotic exchange rate model. In particular, we assume that each speculator follows his own technical and fundamental trading rule. Moreover, a speculator's choice between these two trading philosophies depends on his individual assessment of current market circumstances. Our agent-based model setup is able to explain a number of important stylized facts of foreign exchange markets, including bubbles and crashes, excess volatility, fat-tailed return distributions, serially uncorrelated returns and volatility clustering. A stability and bifurcation analysis of its deterministic skeleton provides us with useful insights that foster our understanding of exchange rate dynamics.
Keywords: D84; F31; G14; 330; Foreign exchange markets; exchange rates; chartists and fundamentalists; agent-based computational economics; stability and bifurcation analysis